Fluoroscopic Guided Fallopian Tube Recanalisation - Bhargava, S (Med J Armed Forces India, 2005)
BACKGROUND: Fluoroscopic fallopian tube recanalisation is a procedure that relieves proximal fallopian tube obstruction with minimal trauma. Commercially available fallopian tube catheterization sets are costly and cumbersome to use. The modified technique used is easy, less traumatic and lessens the procedure and fluoroscopy time. MATERIAL AND METHODS: A headhunter catheter cut 40cm from its tip was introduced into the uterus under direct vision over a 0.035” guide wire. A 50-cm headhunter 3F catheter was passed through tubal ostium. Microguide wire 0.018” (Terumo) was passed into the fallopian tube. On successful recanalisation free peritoneal spill was seen in the peritoneum on injecting contrast through the microcatheter. Fluoroscopic guided fallopian tube recanalisation (FTR) was performed in 21 cases. RESULTS: The procedure was successful with recanalisation of fallopian tubes in 15 cases. Pregnancy was seen in 3 cases (14.2%). Primary infertility was 71.4% and secondary infertility 28.6%. The mean time of the procedure was 21 minutes with a minimum of 10 minutes and maximum of 40 minutes. The fluoroscopy time was between 4 minutes to 20 minutes with a mean of 11 minutes. The patients who conceived had an average age of 28.2 years. CONCLUSION: The modified technique is simpler to perform with low cost, less trauma and procedure time with good results. This study highlights the need of using modified technique for ease of the procedure and reducing fluoroscopy time.